Comparative investigation of NbN and Nb–Si–N films: experiment and theory - Ivashchenko, V.I.; Scrynskyy, P.L.; Lytvyn, O.S.; Butenko, O.O.; Sinelnichenko, O.K.; Gorb, L.; Hill, F.; Leszczynski, J.; Kozak, A.O. (Сверхтвердые материалы, 2014)
NbN and Nb–Si–N films have been deposited by magnetron sputtering of the Nb and Si targets on silicon wafers at various powers supplied to the Nb target. The films have been investigated by an atomic force microscope, X-ray diffraction, X-ray photoelectron spectroscopy, nanoindentaion and microindentation. The NbN films were nanostructured, and the Nb–Si–N films represented an aggregation of δ-NbNx nanocrystallites embedded into the amorphous CSi₃N₄ matrix (nc-δ-NbNx/a-CSi₃N₄). The annealing of the films in vacuum showed that their intensive oxidation occurred at annealing temperature higher than 600 °C. To explain the experimental results on the Nb–Si–N films, first-principles molecular dynamics simulations of the NbN(001)/CSi₃N₄ heterostructures have been carried out. NbN і Nb–Si–N плівки осаджували на кремнієві пластини методом магнетронного розпилення мішеней Nb і Si при різних потужностях розряду на мішені із Nb. Плівки були досліджені за допомогою атомно-силового мікроскопа, дифракції рентгенівських променів, рентгенівської фотоелектронної спектроскопії, нано- і мікроіндентування. NbN плівки були наноструктуровані, тоді як Nb–Si–N плівки являли агрегацію δ-NbNx нанокристалітів, вкраплених в аморфну CSi₃N₄ матрицю (nc-δ-NbNx/ a-CSi₃N₄). Відпал плівок у вакуумі показав, що їх інтенсивне окислення відбувається при температурі вищій, ніж 600 °C. Для пояснення експериментальних результатів по Nb–Si–N плівках проведено моделювання NbN (001)/CSi₃N₄ гетероструктури із перших принципів в рамках молекулярної динаміки. NbN и Nb–Si–N пленки осаждали на кремниевые пластины методом магнетронного распыления мишеней Nb и Si при различных мощностях разряда на мишени с Nb. Пленки были исследованы с помощью атомно-силового микроскопа, дифракции рентгеновских лучей, рентгеновской фотоэлектронной спектроскопии, нано- и микроиндентирования. NbN пленки были наноструктурированные, тогда как Nb–Si–N пленки представляли агрегацию δ-NbNx нанокристаллитов, вкрапленных в аморфную CSi₃N₄ матрицу (nc-δ-NbNx/a-CSi₃N₄). Отжиг пленок в вакууме показал, что их интенсивное окисление происходит при температуре выше, чем 600 °C. Для объяснения экспериментальных результатов по Nb–Si–N пленках проведено моделирование NbN (001)/CSi₃N₄ гетероструктуры из первых принципов в рамках молекулярной динамики. This work was partially supported by STCU Contract No. 5539. The authors are grateful to Dr. Timofejeva, I. I. and Dr. Dub, S. N. for XRD investigations and nanoindentation of the films. The authors are grateful to the directorate of the Summery Institute at Jackson State University for financial support and the possibility to perform large-scale calculations.